Pengembangan Media Pembelajaran Komik Berbasis Flipbook Pada Pembelajaran Bahasa Indonesia Tema 2 Subtema 2 Dongeng Tentang “Kisah Semut dan Merpati” Kelas III di SD IT Salsabila Palembang - Pratiwi, Agustin; Murniviyanti, Liza; Agustina, Juaidah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Learning media has an important role in improving student learning outcomes. Therefore, this study aims to produce a comic learning media product based on flipbooks in Indonesian language learning that is valid, practical, and effective. This study uses R&D (Research and Development) with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The object of this study was grade III students of SD IT Salsabila Palembang. Lack of variation in learning media in Indonesian language learning, especially in fairy tale material. Data collection techniques were carried out using interviews, documentation, observation, questionnaires and tests. The results of the study showed that the flipbook-based comic media developed could be stated as very valid based on the assessment of media experts with an average score of 97.33%, the assessment of material experts with an average score of 90%, and the assessment of language experts with an average score of 91.42%. Flipbook-based comic media was also stated as very practical based on the one-to-one student response questionnaire with a total average score of 93.33% and based on the small group student response questionnaire with an average score of 95% with a very practical category. Then from the test results, students obtained an average score of 90.43% with a very effective category. Based on the results developed by the researcher, it was concluded that the development of flipbook-based comic learning media on fairy tale material met the criteria of valid, practical, effective and feasible to be used in the learning process, especially on fairy tale material.